KAJIAN TEORITIK PENGEMBANGAN KEMAMPUAN BERPIKIR KRITIS-DIALOGIS MAHASISWA MELALUI PENDEKATAN PEMBELAJARAN DEEP DIALOGUE AND CRITICAL THIN-KING (DDCT) DALAM PERKULIAHAN PENDIDIKAN KEWARGANEGARAAN DI LINGKUNGAN PERGURUAN TINGGI MUHAMMADIYAH (PTM) - Zuriah, Nurul (PKn Progresif, 2008)
Learning innovation on Civic Education lecture around universities, especially Muhammadiyah universities, was so much needed in order that the applied learning and lecturing can practice the students? capability of critical and dialogical through the implementation of DDTC (Deep Dialogue and Critical Thinking) model so that it gave maximum contribution in accelerating process of democratic development. The result elemen-tary concept of study of teoritik of ability development critical thinking-dialogis student through the innovation and reorientation of study DDCT in lecturing PKN/CE which is in environment PTM. The learning model inno-vation is conducted that includes various special and general characters, such as: (a) Philosophical based constructivism and Para-digm changes in teaching, learning, and study. (b). The Judicial Base is: UUD?45, UU SPN, PP SNP, and Permen Mendiknas, SK Dirjen Dikti (c) The General Learning Characteristic; and (d) Specific Cha-racteristic of DDCT learning model.